2022
DOI: 10.3389/fcvm.2022.910100
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Volume Overload and Edema in Heart Failure With Reduced Ejection Fraction

Abstract: From a pathogenetic point of view, heart failure (HF) is characterized by the activation of several neurohumoral pathways with a role in maintaining the cardiac output and the adequate perfusion pressure in target organs and tissues. Decreased cardiac output in HF with reduced ejection fraction causes activation of the sympathetic nervous system, the renin angiotensin aldosterone system, arginine-vasopressin system, natriuretic peptides, and endothelin, all of which cause water and salt retention in the body. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…It has been reported that the plasma levels of vasopressin are elevated during the development of heart failure [251][252][253]. While the activation of the V 1a receptors via vasopressin results in the development of vasoconstriction, hypertension, cardiac hypertrophy and heart failure, the activation of the V 2 receptors is associated with fluid retention, leading to the development of volume overload, venous congestion, edema and lung congestion [254][255][256][257][258][259]. Vasopressin not only causes water retention but also results in kidney dysfunction in heart failure patients.…”
Section: Role Of Vasopressin In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…It has been reported that the plasma levels of vasopressin are elevated during the development of heart failure [251][252][253]. While the activation of the V 1a receptors via vasopressin results in the development of vasoconstriction, hypertension, cardiac hypertrophy and heart failure, the activation of the V 2 receptors is associated with fluid retention, leading to the development of volume overload, venous congestion, edema and lung congestion [254][255][256][257][258][259]. Vasopressin not only causes water retention but also results in kidney dysfunction in heart failure patients.…”
Section: Role Of Vasopressin In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…Myocardial remodeling in HFpEF differs from myocardial remodeling in HFrEF, which is caused by the death of cardiomyocytes due to oxidative stress caused by various factors such as ischemia, infection, and toxicity ( Figure 1 ) [ 13 , 14 , 15 ].…”
Section: Main Pathophysiological Mechanisms Involved In the Productio...mentioning
confidence: 99%
“…In HFrEF, decreased cardiac output causes activation of the sympathetic nervous system, the renin-angiotensin-aldosterone system, the arginine-vasopressin system, natriuretic peptides, and endothelin, all of which cause water and salt retention in the body. Thus, activation of the renin-angiotensin-aldosterone system is a primary mechanism in HFrEF, and inhibition of its overexpression is a primary means of treatment in this category of patients [ 15 ].…”
Section: Treatment Of Patients With Hfpefmentioning
confidence: 99%
“…Acting in this multimodal way to increase the atherosclerotic process, Galectin-3 has a central place and represents a target for prevention therapies. At present, statins have shown their effect on lowering the level of Galectin-3 in various studies [ 192 ], but other therapies, such as Quinapril, mineralocorticoid receptor antagonists, and N-acetyllactosamin, were shown to have a positive effect on the level of Galectin-3 [ 193 , 194 , 195 ]. On the other hand, Doxazosin exacerbates the expression of Galectin-3 in cardiomyocytes [ 196 ].…”
Section: Proteomics Of Vulnerable Plaquesmentioning
confidence: 99%